2012
DOI: 10.2135/cropsci2012.01.0054
|View full text |Cite
|
Sign up to set email alerts
|

Development of Leaf Spectral Models for Evaluating Large Numbers of Sugarcane Genotypes

Abstract: Leaf reflectance has been used to estimate crop leaf chemical and physiological characteristics. Sugarcane {Saccharum spp.) leaf N, C, and chlorophyll levels are important traits for high yields and perhaps useful for genotype evaluation. The objectives of this study were to identify sugarcane genotypic variation in leaf hyperspectral reflectance, leaf chemical (chlorophyll, N, and C), and yield (juice sucrose content, commercial recoverable sucrose [CRS], cane yield in tonnes of cane per hectare [TCH], and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…1E-G) with the CV values ranging from 3.8 to 68.3% across years and wavebands (Fig. Zhao et al (2012b) also found that leaf reflectance values had the greatest variation among sugarcane clones at wavelengths of 550 and 710 nm. Similar to the results observed in the CV patterns of canopy reflectance at different wavebands across clones, the two peaks of CV values of reflectance across measurement dates were also found in two wavebands centered at 550 and 800 nm.…”
Section: Variation In Canopy Reflectance Across Clones and At Differementioning
confidence: 73%
See 4 more Smart Citations
“…1E-G) with the CV values ranging from 3.8 to 68.3% across years and wavebands (Fig. Zhao et al (2012b) also found that leaf reflectance values had the greatest variation among sugarcane clones at wavelengths of 550 and 710 nm. Similar to the results observed in the CV patterns of canopy reflectance at different wavebands across clones, the two peaks of CV values of reflectance across measurement dates were also found in two wavebands centered at 550 and 800 nm.…”
Section: Variation In Canopy Reflectance Across Clones and At Differementioning
confidence: 73%
“…Johnson and Richard (2011) suggested that simple models of sugarcane leaf reflectance before maturity could be developed to describe much of the variability in stalk sucrose levels in Louisiana. Our results indicated that it was difficult to develop a quantitative relation between CRS and sugarcane leaf (Zhao et al, 2012b) or canopy reflectance measured during early and mid-growth stages under the conditions of these studies at Canal Point, FL. In the present study, stalk population, cane yield, and sucrose yield were most significantly and positively correlated with canopy reflectance in wavelengths of 800, 980, and 1200 nm (i.e., near-infrared range) in all 3 yr, although these three yield traits correlated with reflectance in other wavebands in 1 or 2 yr (Table 5).…”
Section: Correlation Of Yield Components With Canopy Reflectancementioning
confidence: 74%
See 3 more Smart Citations